The inclusion fostered by a special education service center: A case study of CRAEDI / Governador Valadares (MG) (Revista Contexto & Educação, 2026)
Knowledge of the Special Education Service (SES) and its management is essential to endorse the training of teachers and school managers, as well as the establishment of public policies in education. In this sense, this research aims to analyze the social role of the Centro Municipal de Referência e Apoio à Educação Inclusiva (CRAEDI) of Governador Valadares (MG). The research methodology is a case study. The choice of CRAEDI is based on the peculiarity that its SES goes beyond the model of multifunctional resource rooms, as recommended by Decree 7611/2011 (Brazil, 2011), which provides SES to all schools in the municipal education network from a single center. The results indicate that CRAEDI's SES contributes to the inclusion and improvement of the cognitive, social, and emotional development of children with disabilities and those with high ability/giftedness in regular schools. Furthermore, CRAEDI students have greater chances of entering the job market and participating in social activities, considering their future expectations. The success of CRAEDI's actions is due to the principle of inclusion and accessibility permeating the human competence of its professionals, as well as its physical and technological structure, and its Political Pedagogical Project.
Keywords: Special Education Service; Inclusive education; Multifunctional resource rooms